2023
DOI: 10.1002/jctb.7476
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous nanocomposites based on CeO2 and MgO: preparation, structure and photocatalytic activity

Abstract: BACKGROUNDSelf‐propagating high‐temperature synthesis was used to create mesoporous CeO2 and MgO powders as well as nanocomposites based on them for efficient degradation of organic dyes.RESULTSIt has been investigated how magnesium oxide and cerium oxide interact to affect the crystal structure, morphology and microstructure of the materials produced. It was assumed that CeO2 forms on the surface of MgO while the material's developed surface is preserved. The values of the specific surface area and average po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The photocatalytic and PL properties of the MgO/CeO 2 and MgAl 2 O 4 /CeO 2 systems have received little attention in the literature [35][36][37], with no data available for the MgO/MgAl 2 O 4 /CeO 2 system. Our study has, for the first time, shown that PEO applied to magnesium alloys can generate MgO/MgAl 2 O 4 /CeO 2 coatings suitable for photocatalytic and PL applications.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic and PL properties of the MgO/CeO 2 and MgAl 2 O 4 /CeO 2 systems have received little attention in the literature [35][36][37], with no data available for the MgO/MgAl 2 O 4 /CeO 2 system. Our study has, for the first time, shown that PEO applied to magnesium alloys can generate MgO/MgAl 2 O 4 /CeO 2 coatings suitable for photocatalytic and PL applications.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of processes were used to create PbO nanostructures, including chemical deposition [ 17 ], sol–gel pyrolysis [ 18 ], thermal breakdown [ 19 ], and decomposition under microwave radiation [ 20 ]. Meanwhile, magnesium oxide (MgO) has exceptional surface properties at the nanoscale, due to its polyhedral structure and the formation of Frenkel or Schottky defects at the edge or corner [ 21 , 22 , 23 ]. These characteristics provide the nanomaterials with a large surface area, which makes them useful for cleaning up the environment.…”
Section: Introductionmentioning
confidence: 99%